STRATEGI BERTUTUR DALAM TINDAK TUTUR BERTANYA PADA PROGRAM ACARA AFD NOW - Dewi, Anisa Kumala; Manaf, Ngusman Abdul (Universitas Negeri Padang, 2019)
This research was written to describe the type of speech act in question and its speaking strategy. This type of research is qualitative which uses descriptive methods. The data source of this research is the question utterances used by the host on the AFD Now program on the CNN Indonesia television station. The results of this study are as follows. First, there are 5 types of speech acts to ask, namely (1) the speech act asks who asks for a yes/no answer or yes/no; (2) the speech act asks who asks for information about the elements of the sentence; (3) the speech act asks who asks for an excuse; (4) the speech act asks who asks for opinions; and (5) the speech act asks who asks for a reinforcing answer. The questioning act that is most often used is a questioning act that asks for information yes / no or yes / no as much as 49 data or 36%. Second, there are 4 types of narrative strategies, namely (1) strategies to speak frankly without further ado; (2) the strategy of speaking frankly with the pleasantries of positive politeness; (3) strategies to speak frankly with small talk of negative politeness; (4) strategies speak vaguely. Among the four narrative strategies, the most frequently used strategy is to speak frankly with positive politeness, as many as 31 data from 138 data or 22.8%. The host does not use the strategy of speaking silently or silently because the AFD Now program is an interactive oral dialogue between the emcee and the guest speaker.Â Keywords: Speech Strategy, Speech Acts, Television Station Events.